2013
DOI: 10.4314/jab.v67i0.95048
|View full text |Cite
|
Sign up to set email alerts
|

Effect of graded levels of dry pineapple peel on digestibility and growth performance of rabbit

Abstract: Objectives: A feeding trial was conducted to investigate the effect of the inclusion levels of sun dried pineapple peel (PP) in the diets, on the digestibility and growth performance of rabbits. Methodology and Results: Diets R0 (control), R20, R30 and R40 were formulated by including 0, 20, 30 and 40% of PP. Panicum maximum C1 fodder supplemented the diet of each rabbit. Twenty-four growing rabbits, of 40 to 55 days old, with initial weight 765 ± 128g were used for 70-day trial. Faecal apparent digestibility … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
4
2
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 7 publications
2
4
2
1
Order By: Relevance
“…Interestingly, significantly lower growth performances were found in fish fed high dose of PAPP. Similar results were observed in rabbits fed pineapple peel [62] and pig fed pineapple by-products [63]. This may be attributable to the high fibre contents in pineapple by-products.…”
Section: Tablesupporting
confidence: 85%
“…Interestingly, significantly lower growth performances were found in fish fed high dose of PAPP. Similar results were observed in rabbits fed pineapple peel [62] and pig fed pineapple by-products [63]. This may be attributable to the high fibre contents in pineapple by-products.…”
Section: Tablesupporting
confidence: 85%
“…The incorporation of GLM in the rabbit diets reduced the digestibility of dry matter (dDM), organic matter (dOM) and crude protein (dCP). The digestibility of dry matter (68.54 to 77.71%) observed is higher than values (62 to 67%) obtained by [30], [31] in rabbits, but lower than dry matter intake (77.62 to 85.99%) recorded by [32] [33]. The decrease of organic matter and crude protein digestibility with the inclusion of GLM in diet could be due to the presence of anti-nutritional factors which interfere with the utilisation of dietary nutrients in a various ways, including the reduction of protein digestibility, binding to various nutrients or damaging the gut wall [34] and thereby depressing digestive efficiency [35].…”
Section: B Digestibility Studycontrasting
confidence: 69%
“…The observed crude protein was comparable to the value of 5.11% (Adeyemi et al, 2010) for pineapple peels alone, but higher than the value of 3.69% reported by Omwago et al (2013) for the waste. It was however lower than 6.12% reported by Aboh et al (2013) for pineapple peels. With the crude fibre content observed in this study, Omole et al (2011) opined that PW could be a veritable source of fibre in livestock diets.…”
Section: Chemical Compositions Of Pineapple Waste Wheat Offals and Bcontrasting
confidence: 62%
“…The nitrogen free extract values reflect higher concentration of energy in PW than in WO and BDG in that order. Aside from compositional differences between the wastes, Aboh et al (2013) attributed the observed chemical variations in PW to pineapple varietal differences and supply of fertilizers.…”
Section: Chemical Compositions Of Pineapple Waste Wheat Offals and Bmentioning
confidence: 99%